Morality and the Concept of the Market Seller among Gehamo. Issue 2 (9th July 2019) - Busse, Mark
ABSTRACT: This paper examines the negative moral evaluations of people who buy and resell fresh food by Gahuku and Gehamo people in and around Goroka, the capital of Eastern Highlands Province, Papua New Guinea. During my fieldwork from 2010 to 2015, vendors in the Goroka fresh food market argued that the value of fresh food should be based on the work that people did to produce it rather than on price competition, or on supply and demand. An examination of market vendors' practice of 'giving extra' to customers, and the responses of vendors who resold food to negative moral evaluations of their activities, led me to an examination of the morality of production in relation to land, ancestors, and social relations; the morality of the marketplace; as well as ideas about what makes someone a good social person. Drawing on Erik Schwimmer's (1979) discussion of the concept of work in Melanesian societies, I argue that vendors in the Goroka market continue to emphasize use value and their own identification with the food that they are selling rather than the exchange value of alienated produce. While marketplaces are the apparent locus par excellence of capitalist economic activity, a consideration of the morality of Goroka market vendors leads to the caution that just because one sees something that looks like a marketplace in which people are engaging in commodity transactions does not necessarily mean that it is a marketplace in which people are engaging in commodity transactions. Similarly, just because something looks like a price does not necessarily mean that it is a price. Those considerations, in turn, lead to a re‐examination of Kenneth Read's (1955) characterization of morality and personhood among Gahuku in light of contemporary market exchange. Abstract :